Pengaruh Pengetahuan Investasi, Modal Minimal dan Informasi Produk Terhadap Minat Berinvestasi Mahasiswa KSPM di Provinsi Bali - Komang Sri Widiantari; Ni Komang Indah Oktaliasari (UNHI Press, 2022)
The aim of this study was to determine the influence of investment knowledge, minimum capital, partial product information on investment returns. The population consisted of KSPM students in the province of Bali and a sample of 76 people. Analytical techniques in this study, namely: validity test, reliability test, classical hypothesis test, multiple linear regression analysis, coefficient of determination test and test t. The influence of the independent variable on investment interest rate is 53.7%. Scholars may suggest that KSPM students in Bali Province deepen their investment knowledge, such as attending seminars or learning directly from those who have invested and are always looking Find the latest investment information. Keywords: investment knowledge, minimum capital, and investment interest